2018
DOI: 10.1097/pec.0000000000001547
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Lung Abscess

Abstract: The diagnosis of lung abscess can be difficult to make and often requires imaging beyond plain chest x-ray. The decision to further image with computed tomography should be weighed against the risks of radiation exposure, especially in pediatric patients. In addition, the cost and potential impact on length of stay from obtaining computed tomography scans should be considered. In this report, we describe a case of lung abscess made immediately using point-of-care ultrasound in the emergency department. To our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Lung ultrasound has certain advantages in the examination of various lung diseases ( 27 ). Clara Kraft et al ( 28 ) reported a case of pediatric pulmonary abscess, which also showed elliptical consolidation on ultrasound, with a surrounding hyperechoic capsule. In addition, some authors suggest that further identification of the presence of pneumothorax is necessary when a lung abscess is discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ultrasound has certain advantages in the examination of various lung diseases ( 27 ). Clara Kraft et al ( 28 ) reported a case of pediatric pulmonary abscess, which also showed elliptical consolidation on ultrasound, with a surrounding hyperechoic capsule. In addition, some authors suggest that further identification of the presence of pneumothorax is necessary when a lung abscess is discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lung ultrasound has demonstrated its role in the diagnosis of this condition. On ultrasound, the abscess is seen as a well-demarcated capsular structure surrounding a hypoechoic core non-vascularized and follows its evolution over time [41] (Figure 4). In this way, additional investigations, such as computed tomography (CT), can be avoided with significant radiation protection benefits, especially in the pediatric age group.…”
Section: Lung Abscessmentioning
confidence: 99%